Our bodies, their battlefields : war through the lives of women - Lamb, Christina (Scribner, an imprint of Simon & Schuster, 2020)
"In Our Bodies, Their Battlefields, longtime intrepid war correspondent Christina Lamb makes us witness to the lives of women in wartime. An award-winning war correspondent for twenty-five years (she's never had a female editor) Lamb reports two wars--the "bang-bang" war and the story of how the people behind the lines live and survive. At the same time, since men usually act as the fighters, women are rarely interviewed about their experience of wartime, other than as grieving widows and mothers, though their experience is markedly different from that of the men involved in battle. Lamb chronicles extraordinary tragedy and challenges in the lives of women in wartime. And none is more devastating than the increase of the use of rape as a weapon of war. Visiting warzones including the Congo, Rwanda, Nigeria, Bosnia, and Iraq, and spending time with the Rohingya fleeing Myanmar, she records the harrowing stories of survivors, from Yazidi girls kept as sex slaves by ISIS fighters and the beekeeper risking his life to rescue them; to the thousands of schoolgirls abducted across northern Nigeria by Boko Haram, to the Congolese gynecologist who stitches up more rape victims than anyone on earth. Told as a journey, and structured by country, Our Bodies, Their Battlefields gives these women voice."--Amazon.